Analisis Semiotika Foto Jurnalistik pada Portal beritasumut.com Dalam Rubrik Peristiwa Edisi HUT RI Ke-78 - Aulia Lutfi Wirayudha Irawan; Fakhrur Rozi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Mass communication media that are used to convey information to audiences broadly and thoroughly are referred to as mass media. One of the news portals that is a media of information or news that publishes events or events is beritasumut.com. This study uses a qualitative descriptive method, where qualitative research is research whose results are not based on statistical calculations. This study uses Roland Barthes’ Theory, where Barthes' analysis is divided into several stages of analysis, namely denotation and connotation. In Roland Barthes' semiology, denotation is the first level of signification system, while connotation is the second level. The results of the research show that photojournalism in the Events rubric has many meanings and contains social messages to invite readers to always be careful around their environment and do things which is useful. It also has the same value, namely informative value, where the content of the news conveys information. Keywords: Semiotics, Photos, Journalism, Portal, beritasumut.com